A novel R3 MYB transcriptional repressor associated with the loss of floral pigmentation in Iochroma. Issue 3 (12th October 2017) - Gates, Daniel J.; Olson, Bradley J. S. C.; Clemente, Tom E.; Smith, Stacey D.
Summary: Losses of floral pigmentation represent one of the most common evolutionary transitions in flower color, yet the genetic basis for these changes has been elucidated in only a handful of cases. Here we used crossing studies, bulk‐segregant RNA sequencing, phylogenetic analyses and functional tests to identify the gene(s) responsible for the transition to white flowers in Iochroma loxense . Crosses between I. loxense and its blue‐flowered sister species, I. cyaneum, suggested that a single locus controls the flower color difference and that the white allele causes a nearly complete loss of pigmentation. Examining sequence variation across phenotypic pools from the crosses, we found that alleles at a novel R3 MYB transcription factor were tightly associated with flower color variation. This gene, which we term MYBL1, falls into a class of MYB transcriptional repressors and, accordingly, higher expression of this gene is associated with downregulation of multiple anthocyanin pigment pathway genes. We confirmed the repressive function of MYBL1 through stable transformation of Nicotiana . The mechanism underlying the evolution of white flowers in I. loxense differs from that uncovered in previous studies, pointing to multiple mechanisms for achieving fixed transitions in flower color intensity.